DYNAMIC CHARACTERISTICS OF INTERNAL CONTACT OF ROLLING BEARINGS UNDER DIFFERENT DEGREES OF FAILURE - TU WenBing; YANG JinWen; LUO Ya; REN JiWen (Jixie qiangdu)
The change in the internal contact state caused by the failure of the rolling bearing is an important factor that causes the change in its vibration characteristics. According to the contact form of the fault and the rolling element,this paper considered the different sizes of the fault evolution process,and established the dynamic finite element model of the multi-body contact of the cylindrical roller bearing with different degrees of failure. The effectiveness of the model was verified by the experiment on the outer ring fault of the rolling bearing. Based on the explicit dynamics method,the dynamic contact force between the rolling element and each component and the contact strain of the fault area was analyzed,then the influence law of different fault degrees on the internal dynamic characteristics of the bearing and the change law of the contact deformation under the fault condition were revealed. The results show that the contact force of the rolling elements with the components is reduced when the defects are crossed. As the degree of failure increases,the fluctuation of the internal contact force of the bearing becomes more and more intense,but the fluctuation frequency and amplitude of the contact strain decrease. In the loading area,the rolling elements of faulty bearing are in contact with both sides of the cage pocket,which causing a negative contact force. The fault tends to expand along the rolling direction of the rolling element. The research conclusion can provide a theoretical basis for fault diagnosis and residual life prediction of rolling bearings.